2017
DOI: 10.1371/journal.pone.0189518
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation triggers widespread responses and alters large-scale functional connectivity in the rat brain

Abstract: Vagus nerve stimulation (VNS) is a therapy for epilepsy and depression. However, its efficacy varies and its mechanism remains unclear. Prior studies have used functional magnetic resonance imaging (fMRI) to map brain activations with VNS in human brains, but have reported inconsistent findings. The source of inconsistency is likely attributable to the complex temporal characteristics of VNS-evoked fMRI responses that cannot be fully explained by simplified response models in the conventional model-based analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…The present study has several limitations. First, previous studies have reported that the frequency of cervical VNS used in different I/R injuries ranges from 2 to 20 Hz (Cao et al, 2017; Stauss, 2017; Mirza et al, 2018). In the present study, we evaluated the effect of VNS at 5 Hz in the retinal I/R model.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has several limitations. First, previous studies have reported that the frequency of cervical VNS used in different I/R injuries ranges from 2 to 20 Hz (Cao et al, 2017; Stauss, 2017; Mirza et al, 2018). In the present study, we evaluated the effect of VNS at 5 Hz in the retinal I/R model.…”
Section: Discussionmentioning
confidence: 99%
“…When the stimulation patterns and dynamics of functional networks during VNS were examined by fMRI, the vagus nerve was found to convey signals to the brain through the polysynaptic neuronal pathways, by projecting to the brainstem nuclei (NTS, locus coeruleus), subcortical areas and lastly to the cortex (Henry, 2002;Ressler and Mayberg, 2007), thus covering the entire CAN. fMRI and a spatially independent component analysis were utilized in a recent experimental study (Cao et al, 2017). That study demonstrated that VNS activated 15 out of 20 brain networks and that the activated regions covered > 75% of the brain volume.…”
Section: The Inflammatory Reflex or Neuroinflammation In The Pathogenmentioning
confidence: 99%
“…The fMRI data were processed using Analysis of Functional Neuroimages (AFNI, [37]) and the FMRIB Software Library (FSL, [38]). The fMRI data were first corrected for motion and slice timing before being spatially smoothed as per one of the prior works [9], [39]. The fMRI time series were detrended by regressing out the linear trend voxel by voxel.…”
Section: Post-processingmentioning
confidence: 99%